ZigBee devices for distributed generation management: field tests and installation approaches - Batista, Nelson (2013)
The implementation of a renewed electrical grid is urgent and it must be flexible, reliable, efficient and manageable. In this context, sensors and actuators play an important part, thus being the “nerve cells” of the grid. The ZigBee standard is receiving an increased acceptance by the industry and is experiencing a fast implementation. Hence, several new field tests are presented in this paper in order to study the implementation challenges of different sensor systems, especially wireless ZigBee devices installation approaches in distributed generation sites for monitoring, management and control. Finally, conclusions are duly drawn.